Sepsis-Akut Kidney Injury pada Urosepsis - Sudarsono; Palu, Raphael Putra; Aditianingsih, Dita (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2018)
Sepsis is a life-threatening condition caused by a dysregulated immune response to infection. Sepsis mortality increases with acute kidney injury and patients with acute kidney injury worsen with sepsis. It is interesting to note that most of the clinical trials on sepsis treatment that derived from the results of translational researches are a failure. This is because of the complexity of human sepsis in comparison with animal models and the improper matching of the animal models to the individual patient. It is possible that the main mechanism of sepsis induction in each patient with the variety causes of sepsis might be different. Immune response to sepsis depends on genetic background, route of immune activation and organisms. Urosepsis is type of infection that cause AKI and septic shock. Specific treatment of sepsis induced acute kidney injury in individual patient according to the specific immune response characteristic might be a more proper strategy. Report the case of a female aged 50 years, entered into RSCM with primary complaints of unconsciousness, and diangnosed with acute kidney injury et causa urosepsis. Complications acute kidney injury, inbalance electrolite and pneumonia were arised. Monitoring macrocirculation, tissue perfusion parameters, antibiotic and intermitten hemodialisis were performed in patient to recover.